Kedudukan Hak Waris Bagi Wanita Yang Telah Pindah Agama Dalam Sistem Hukum Waris Adat Bali : (Studi Putusan Nomor 2826 K/Pdt/2017) (International Forum of Researchers and Lecturers, 2024)
This research aims to find out about the position of inheritance rights for Balinese women who have changed religions based on the case study of Cassation Decision Number 2826 K/Pdt/2017. The background of the research, that the biological daughter of the heir who has converted to religion demands her right to be made an heir, where as it is well known that Balinese society has a patrilineal kinship system (purusa), which means that the heir will fall to the son. This type of research is normative legal research with the approach applied in this normative legal research is a conceptual approach and a case approach. The results of the analysis of the research, the Decree of the Main Assembly of Pakraman Village Bali in 2010 Number: 01/Kep/Psm-3/X/2010 regarding the Results of Pesamuhan Agung III MUDP Bali which states that Balinese women receive half of the purusa inheritance rights after deducting 1/3 for heirlooms and preservation interests. However, this does not apply to Balinese women who have converted (from Hinduism to other religions). This is because as heirs who follow Balinese inheritance law, heirs must have the responsibility to take care of all the obligations of their ancestors both in terms of religious obligations and maintenance of shrines. Therefore, if a child chooses to change religion, the legal consequences will be that the heir or child does not have rights and obligations towards the heir, family and custom.